In silico screening of potential antidiabetic phytochemicals from Phyllanthus emblica against therapeutic targets of type 2 diabetes. (10th February 2020) - Sharma, Priyanka; Joshi, Tushar; Joshi, Tanuja; Chandra, Subhash; Tamta, Sushma
Abstract: Ethnopharmacological relevance: Phyllanthus emblica Linn. (Syn. Emblica officinalis Gaertn.), has been used to cure many ailments of human beings. Literature survey demonstrates that it has many pharmacological activities i.e. antidiabetic, antioxidant, anti-microbial, antifungal, antiallergic, antiviral, and anticancer properties. Aim of the study: The present study aimed to identify the novel plant-derived antidiabetic compounds from P. emblica to understand the molecular basis of antidiabetic activities. Material and methods: Text mining analysis of P. emblica and its disease association was carried out using server DLAD4U. Due to the highest score of P. emblica with diabetes, the virtual screening of a phytochemical library of P. emblica against three targets of diabetes was carried out. After that FAF-Drug4, admetSAR and DruLiTo servers were used for drug-likeness prediction. Additionally, pharmacophore modeling was also carried out to understand the antidiabetic activity of screened compounds. Results: The docking scores, drug-likeness and pharmacophore studies found that Ellagic acid, Estradiol, Sesamine, Kaempferol, Zeatin, Quercetin, and Leucodelphinidin are potential antidiabetic compounds. Conclusions: Our study shows that phytochemicals of P. emblica are very potential antidiabetic candidates. Using the modern techniques these molecules could be used to develop an effective antidiabetic drugs from a natural resource. Graphical abstract: Image 1